Effect of Giving Chocolate Drink (Theobroma Cacao) on Reducing Primary Dysmenorrhea Pain Scale in Adolescents: A Pre-Experimental Study - Melia Rahma; Ririn Anggraini; Wika Sepiwiriyanti; Rani Purnama Sari (Lentera Perawat, 2025)
Menstruation occurs due to an increase in PGF2 and PGE2 levels, where these prostaglandins can cause contractility in the uterus, causing menstrual pain or what is called primary dysmenorrhea. Primary dysmenorrhea can be treated with pharmacological and non-pharmacological therapies. One of the non-pharmacological therapies to reduce primary dysmenorrhea pain is by giving chocolate drinks (Theobroma cacao) containing magnesium, theobromine and flavonoids that can reduce primary dysmenorrhea pain. The purpose of this study was to determine the effect of giving chocolate drinks on reducing the primary dysmenorrhea pain scale in Bakti Ibu 2 Palembang junior high school students. This research design uses Pre Experimental quantitative research (one group pre test post test). The sampling method in the study used was Non Probability Sampling with Purposive Sampling technique.  The number of respondents was 22 including drop out. The instrument used was a pain scale observation sheet using the Numeric Rating Scale (NRS). The p-value is 0.000 (<0.05) which means that there is an effect of giving chocolate drinks on reducing the pain scale of primary dysmenorrhea in female students of SMP Bakti Ibu 2 Palembang. From this study it can be concluded that there is an effect of giving chocolate drinks (Theobroma cacao) on reducing the pain scale of primary dysmenorrhea in adolescents.